Blockage of Potassium Channel Inhibits Proliferation of Glioma Cells Via Increasing Reactive Oxygen Species - Hu, Li (Oncol Res, 2014)
The potassium (K(+)) channel plays an important role in the cell cycle and proliferation of tumor cells, while its role in brain glioma cells and the signaling pathways remains unclear. We used tetraethylammonium (TEA), a nonselective antagonist of big conductance K(+) channels, to block K(+) channels in glioma cells, and antioxidant N-acetyl-l-cysteine (NAC) to inhibit production of intracellular reactive oxygen species (ROS). TEA showed an antiproliferation effect on C6 and U87 glioma cells in a time-dependent manner, which was accompanied by an increased intracellular ROS level. Antioxidant NAC pretreatment reversed TEA-mediated antiproliferation and restored ROS level. TEA treatment also caused significant increases in mRNA and protein levels of tumor-suppressor proteins p53 and p21, and the upregulation was attenuated by pretreatment of NAC. Our results suggest that K(+) channel activity significantly contributes to brain glioma cell proliferation via increasing ROS, and it might be an upstream factor triggering the activation of the p53/p21(Cip1)-dependent signaling pathway, consequently leading to glioma cell cycle arrest.